Incorporating Market Information into the Construction of the Fan Chart - Kannan, Prakash (IMF Working Papers; Working Paper ;, 2009)
This paper develops a simple procedure for incorporating market-based information into the construction of fan charts. Using the International Monetary Fund (IMF)'s global growth forecast as a working example, the paper goes through the theoretical and practical considerations of this new approach. The resulting spreadsheet, which implements the approach, is available upon request from the authors.